Modinomics 1.0 and the Indian Economy. (January 2020) - Esho, Hideki
In this study, we recapitulate the economic policies/measures implemented by Narendra Modi in his first five-year term (2014–2019), referred to as 'Modinomics'. It rests on two pillars, namely growth strategy and anti-poverty programmes, represented by the 'Make in India' and 'JAM trinity' initiatives, respectively. Further, we assess the economic performance achieved in his first term. Macro-economic indicators, such as economic growth and inflation rates, show satisfactory results; however, we do not find enough evidence of the main objective of 'Make in India' being fulfilled, which is 'to make India a global hub of manufacturing, design, and innovation'. The continuation/aggravation of 'jobless growth' is concerning; thus, India should adapt export-oriented industrialization strategy to enhance the viability of 'Make in India' and create enough jobs opportunities. JEL: E24, E61, N15, N35, N65